Pengaruh Reputasi KAP Terhadap Reaksi Investor Melalui Pergantian KAP Secara Voluntary Pada Perusahaan Indeks LQ 45 yang Terdaftar di Bursa Efek Indonesia - Lydia Victoria; Bahtiar Effendi (Universitas Matana, 2020)
The purpose of this study is to investigation over the influence of Accounting Firms Reputation to investor reaction by Switching in accounting firms as a intervening variable (mediation). In this study investor reaction wil be obtained from abnormal return as a scale ratio. Total of all the samples that use in this study is 125 company from LQ45 in Indonesian Stock Exchange from 2014-2018. The samples are acquired using purposive sampling method, the data is acquired from annual reports that publish by the company to investor. This study is use path analysis because there is an intervening variable in this study. The result of this research is obtained that there is an influence from accounting firms reputation to switching in accounting firms, then switch in accounting firms as an intervening variable is able to give an indirect effect from accounting firms reputation to investor reaction, there is no direct effect between each variable of accounting firms reputation and switch in accounting firms to investor reaction (abnormal return).